The Determinants of Complementary Feeding Introduction Vary According to the Type of Food and Infants’ Ages: A Cohort Study—ClaB, Brazil - Almeida, Maiara Aparecida Mialich [UNESP]; Rossato, Sinara Laurini [UNESP]; Ferrari, Anna Paula [UNESP]; de Barros Gomes, Caroline [UNESP]; Tonete, Vera Lúcia Pamplona [UNESP]; de Lima Parada, Cristina Maria Garcia [UNESP]; de Barros Leite Carvalhaes, Maria Antonieta [UNESP] (Springer Nature, 2022)
Introduction: Food inadequacies in the first 6 months of life are considered a global problem, with an emphasis on early complementary feeding introduction (CFI). This study aimed to identify the determinants of CFI. Methods: A birth cohort study (N = 641). Data on infant feeding was collected before 30 days, and at 2, 4, and 6 months of age and, at baseline, data regarding socioeconomic status, demographics, maternal and infant health, obstetric history, and infant care. The hypothesis was that the risk determinants for early CFI vary according to the type of food and the age range of this introduction. Twelve Cox regression models were fit with four outcomes (formula; other types of milk; other beverages; and solid/semi-solid foods) considering three different age ranges of the infant at their introduction (< 2 months, 2–4 months, and 4–6 months). Results: The introduction of the four food groups analyzed was early (median ages of introduction: formulas = 45 days; other milks = 135 days; other beverages = 120 days; solids and semi-solids = 135 days). The determinants that increased the risk of introducing formulas before 2 months were: primiparity, employed without maternity leave, mothers with unsatisfactory prenatal counseling and those who had cesarean sections. Not living with a partner, infant pacifier use at 2 months of age had a higher risk of introducing formula between 2 and 4 months of age. Non-white skin color, more than 35 years old, low maternal education, and lower family income increased the risk of introducing other types of milk between 2 and 4 months of age. Between 4 and 6 months of age, adolescent and low education level mothers had a higher risk of introducing other types of milk, unemployed was a protective factor against the introduction of other foods and beverages in this age group. Conclusions: The determinants of early CFI varied according to the type of food and the age of introduction.
Keywords: Breastfeeding; Complementary feeding; Epidemiology; Food practices; Infant nutrition